Rivaroxaban-induced acute pancreatitis - Sirkeci, Özgür; Erkuş Sirkeci, Emel; Taşel, Belma (The European Research Journal, 2019)
Rivaroxaban is a direct factor Xa inhibitor and has been safely used since 2008. It is used for the detection of atrial fibrillation and venous thromboembolism. Pancreatitis is one of the rare but dangerous side effects of rivaroxaban. The case of a 53-year-old female patient that developed in the third month of drug usage was evaluated, and it was confirmed after a full analysis was conducted that excluded all other factors, such as biliary calculus, alcohol usage, hypertriglyceridemia, biochemical parameters, ultrasonography and computed tomography that the patient’s condition was caused by the use of Rivaroxaban. The aim of this case presentation is to indicate that awareness should be increased regarding the risks of using the drug Rivaroxaban, as it could lead to drug-induced pancreatitis, even though this is rare.